2019
DOI: 10.2478/sbe-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gender and Education on Decision-Making

Abstract: In this article we investigated the predominance of six unique dimensions of decisionmaking. We defined those dimensions as rationality, acuity, autonomy, openness, control, and emotion-neutrality. Our data is based on an online survey conducted on a global scale. From this survey, we received a total of 356 responses, of which 204 (57.3%) are females, and 152 (42.70%) are males. Of the respondents, 139 (39.04%) work in the education sector as teachers, academicians, lab instructors, course assistants and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…The results of the present study indicate that teachers make different disciplinary decisions regarding student offenders in schools depending on school affiliations. This finding agrees with Mostert and Gulseven (2020) study which suggest that female respondents perceive themselves to be less emotionneutral, a finding that is amplified in the education sector.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of the present study indicate that teachers make different disciplinary decisions regarding student offenders in schools depending on school affiliations. This finding agrees with Mostert and Gulseven (2020) study which suggest that female respondents perceive themselves to be less emotionneutral, a finding that is amplified in the education sector.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, few studies available on educational settings are related to literature on decision making, but not on group polarization. For example, Mostert and Gulseven (2020) suggested that female respondents perceive themselves to be less emotion-neutral, a finding that is amplified in the education sector. Thus, female teachers are more likely to make emotional decisions.…”
mentioning
confidence: 99%
“…This gender difference determines the individual in decision making. In addition, gender also determines the trust, commitment, communication, and conflict handling of consumers towards their loyalty to a service or product (Jacques & Osman, 2019). Other studies also state that a person's consumption and tastes are shaped by gender, where there are certain differences between men and women.…”
Section: Resultsmentioning
confidence: 99%
“…The decision-making process in an educational organization is similar to any other business organizations since both aim to achieve a certain set of goals. In addition, emotions play an important role in the decision-making process [1]. Nevertheless, effective decision-making is not just making choices but it also involves the process of identifying problems, listing and selecting alternatives, implementing alternatives and solutions, and evaluating to know which alternative is the best and has the highest chances of success.…”
Section: Decision Making Skillsmentioning
confidence: 99%